Editor's Note: The Project of Moral Inclusiveness Embedded in Critical Realism of The Socio-Scientific Paradigm - Masud Choudhury (University of Darussalam Gontor Press, 2023)
On the over-encompassing cosmic meaning of the moral and material law of unity of knowledge between diverse entities, only recently, the hard sciences have opened to the study of the nature, logic, and implications of consciousness as the moral phenomenology of the order and scheme of the theory of knowledge, and of Being and Becoming in completeness of socio-scienti℀c inquiry. The highest echelons of the study of ontological investigation of Critical Realism of the Core of Science belongs to the study of moral phenomenology of the learning matter-material unified universe. On these substantive issues and the subtle studies that emanate, there are the following sparce ones.